Perilaku Pencegahan ISPA di Wilayah Kerja Puskesmas Bunut Kabupaten Pelalawan - Zul Akbar; Reno Renaldi; Oktavia Dewi; Novita Rany; Abdurrahman Hamid (LPPM Hang Tuah Pekanbaru, 2023)
Acute Respiratory Infection (ISPA) is one of the most contagious diseases and the most common cause of death that occurs in children in developed countries. The mortality rate caused by ISPA is almost four million people every year, and 98% is caused by Acute Respiratory Infection. Pneumonia cases in 2018 decreased, in 2013 the percentage of pneumonia was 1.6% while in 2018 increased to 2.0%, and Bunut Public Health Center obtained an ISPA proportion from the year 2018 – 2020 amount of 16%. The purpose of this research was to find out the behavior of ISPA prevention in the work area of Bunut Public Health Center Pelalawan Regency. This research employed a quantitative research cross-sectional analytic approach. This research was conducted from August – September 2021. The respondents in this research were 70 respondents in the work area of Bunut Public Health Center Pelalawan Regency. This research employed univariate, bivariate, and multivariate analysis. The research results that obtained p-value < 0.05 were such as immunization status variable (p=0.000) with POR = 32.763, occupation variable (p=0.024) with POR = 0.183, parents’ role variable (p = 0.032) with POR = 5.300 and not correlated variables namely attitude (p=0.917) with POR = 0.918, education (p=0.649) with POR = 1.403, smoking (p=0.299) with POR 0.649. Parents’ role is necessary for increasing awareness about the danger of ISPA and parents’ active role towards the infant and toddler health status and to give complete basic immunization to prevent ISPA even though the parents are busy working.